Construction & Design Techniques Using In The Curtain Wall System - Jeyamohan, K. (Annual Transactions-2021, IESL Northern Chapter, 2021)
This paper describes the construction and design techniques of the curtain wall system which are currently used in the curtain wall Industry. Nowadays, Unitized & Semi Unitized are major types of curtain wall systems used in the industry. Unitized curtain wall system is commonly used for high-rise building and also semi-unitized curtain wall system is used for low-rise building due to construction & installation issues. The curtain wall panel is mainly made by using aluminum extrusion with glass panels. Structural adequacy, provision of movement, and control of thermal & weather tightness are the major design considerations in the curtain wall design. Some of the techniques are used in the industry to control the above design considerations within the allowable limits. Stack joint design is important for the provision of vertical & horizontal movement between the panels of the curtain wall system. Also moment, shear, axial, deflection and lateral torsional buckling checks are major capacity checks involved in the curtain wall design. Using anti-buckling clip technology in the mullion profile is an effective method to avoid lateral torsional buckling failure in the curtain wall system.
Keywords: Unitized Curtain wall; Extrusion; Stack Joint; Mullion